Strengthening Cooperatives and Entrepreneurship Development to Reduce Poverty and Unemployment in Indonesia - Ahmad Asroni (International Journal of Management and Business Economics, 2025)
Poverty and unemployment remain major socio-economic challenges in Indonesia and continue to hinder national development and social welfare improvement. The relatively high rate of unemployment and poverty indicates that economic growth has not fully succeeded in creating equitable prosperity for all levels of society. In this context, cooperatives play a strategic role as people-based economic institutions that can empower communities, strengthen micro and small businesses, and create employment opportunities. This study aimed to analyze the role of cooperatives in reducing poverty and unemployment through entrepreneurship development in Indonesia. The study employed a qualitative approach using library research methods. Data were collected from books, scientific journals, government reports, publications from Statistics Indonesia (BPS), and other relevant academic sources related to cooperatives, entrepreneurship, poverty, unemployment, and community economic empowerment. Data analysis was conducted using content analysis techniques to identify patterns and relationships between cooperatives and entrepreneurship development in reducing socio-economic problems. The findings revealed that cooperatives contribute significantly to poverty and unemployment reduction through entrepreneurship education, vocational training, business mentoring, and access to capital for micro, small, and medium enterprises (MSMEs). Cooperatives also encourage the emergence of new entrepreneurs, improve community productivity, and strengthen local economic resilience. Furthermore, cooperatives support inclusive and sustainable economic development by promoting democratic economic participation and social solidarity among community members. Therefore, strengthening cooperatives through supportive government policies, entrepreneurship education, and institutional innovation is essential for achieving sustainable economic development and improving social welfare in Indonesia.